Mitral Valve Prolapse in Dar-es-Salaam, Tanzania: Clinical and Echocardiographic Profile (Tanzania Medical Journal, 2007)
Background: Mitral Valve Prolapse is a common, usually a benign disease. If recognized early, it has a good prognosis and saves the doctor and patients from embarrassing mismanagement.Broad Objective: To determine the prevalence of Mitral Valve Prolapse among patients referred to our cardiac clinic with provisional diagnosis of Mitral Valve Prolapse.Study Design: Descriptive and analytical hospital based study Study Setting: Hindul Mandal Hospital, Dar es Salaam, Tanzania.Measures of Outcome: Identifying the clinical features and characterizing echocardiographic features specific for diagnosing Mitral Valve Prolapse. Subjects: Three hundred and forty patients with provisional diagnosis of mitral valve prolapse referred to a cardiac clinic at Hindu Mandal Hospital Interventions: A detailed past and recent cardiac history, clinical examination as well as echocardiographic evaluation were performed.Results: Among 340 patients with provisional diagnosis of mitral valve prolapse, 224 (65.9%) were confirmed to have mitral valve prolapse. The five common symptoms were chest pain, palpitations, shortness of breath, fatigue and dizziness. A subgroup of 25 patients with mitral valve prolapse who had mitral regurgitation had thicker and longer leaflets than those patients who had no mitral regurgitation (P